Shear Capacity of Open Sandwich Steel Plate-Concrete Composite Slab: Experimental and Analytical Studies - Lili Wu; Lipei An; Jiawei Li (Advances in Civil Engineering)
Considering that the fixed crack model by default of the general finite element software was unable to simulate the shear softening behavior of concrete in the actual situation, a rotational crack model based on the modified compression field theory developed by UMAT (user material) of ABAQUS software was proposed and applied to the nonlinear analysis, and a numerical simulated model for the steel-concrete composite slab was built for shear analysis. Experimental studies and numerical analyses were used to investigate the shear load-carrying capacity, deformation, and crack development in steel plate-concrete composite slab, as well as the effects of the shear span ratio and shear stud spacing on the shear performance and the contribution of the steel plate and the concrete to the shear performance. Shear capacity tests were conducted on three open sandwich steel plate-concrete composite slabs and one plain concrete slab without a steel plate. The results indicated that the shear-compression failure mode occurred primarily in the steel plate-concrete composite slab and that the steel plate sustained more than 50% of the total shear force. Because of the combination effect of steel plate, the actual shear force sustained by the concrete in the composite slab was 1.27 to 2.22 times greater than that of the calculated value through the Chinese Design Code for Concrete Structures (GB 50010-2010). Furthermore, the shear capacity of the specimen increases by 37% as the shear stud spacing decreases from 250 mm to 150 mm. By comparing the shear capacity, the overall process of load deformation development, and the failure mode, it was shown that the simulation results corresponded with the experimental results. Furthermore, the numerical simulation model was applied to analyze the influence of some factors on composite slab, and a formula of shear bearing capacity of slab was obtained. The results of the formula agreed with the test result, which could provide references to the design and application of steel plate-concrete composite slab.